Mengungkap Praktik Akuntansi Pendapatan oleh Para Guru Honorer TK - Thalib, Mohamad Anwar; Monantun, Widy Pratiwi (Penerbit Goodwood, 2023)
Purpose: This study aims to reveal income accounting practices by kindergarten teachers based on non-material values. Method: This study uses an Islamic paradigm with an Islamic ethnomethodological approach. There are five data analysis stages: charity, knowledge, faith, revelation information, and courtesy. Result: The results of the study show that there are three ways of practicing income accounting that are implemented by kindergarten teachers, namely first, income accounting practices that originate from the profession of kindergarten teachers; secondly, the accounting practice of income originating from side business income; the three methods of recording revenue accounting in memory. Nonmaterial values condition these three accounting practices through patience and persistence. Limitation: The limitation of this study is that the study's results need to provide documentation related to the method of recording income accounting by honorary kindergarten teachers. Contribution: The contribution of this research is that the results of this study add to the repertoire of accounting knowledge, especially related to income accounting, by honorary kindergarten teachers. The outcome of this study is to identify the non-material values that are most important for honorary teachers in managing their income. This can help identify the aspects that influence financial decisions. Novelty: The novelty of this research is that the results show that the practice of income accounting by honorary kindergarten teachers is based on non-material values.